Conditioning monitoring of stamping blanking oil using fourier transform infra-red spectroscopy - Mohd Fairuz, Dimin; Mohamad Nizam, Ayof; Mohd Zaki, Sharifuldin; Izzad Jauhari, Sarlan; Na'ain, Shari (Universiti Malaysia Pahang (UMP), 2010)
MUCEET 2009 is organized by Malaysian Technical Universities Network (MTUN) comprising of Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussein Onn (UTHM), Universiti Teknikal Melaka (UTeM) and Universiti Malaysia Pahang (UMP), 20th - 22nd June 2009 at M. S. Garden Hotel, Kuantan, Pahang.